Polymorphisms of matrix metalloproteinases affect the susceptibility of esophageal cancer: Evidence from 20412 subjects, systematic review and updated meta-analysis - Chen, Hai; Xu, Xianquan; Hua, Congshu; Zhang, Heng; Jian, Junling; Ge, Tengfei; Xie, Jianfeng; Yu, Zaicheng (Medicine (Baltimore), 2021)
The results of how matrix metalloproteinases (MMPs) polymorphisms affect esophageal cancer (EC) risk are not consistent, especially for MMP1,2,7 and 9. A meta-analysis focused on the impact of MMPs to digestive cancers, but not a precise analysis to EC, therefore, we designed the current study to make a clear understanding of the association between MMPs polymorphisms and EC.BACKGROUNDThe results of how matrix metalloproteinases (MMPs) polymorphisms affect esophageal cancer (EC) risk are not consistent, especially for MMP1,2,7 and 9. A meta-analysis focused on the impact of MMPs to digestive cancers, but not a precise analysis to EC, therefore, we designed the current study to make a clear understanding of the association between MMPs polymorphisms and EC.Up to March 2020, we searched several databases to find case-control cohorts concerned about the risk of MMPs polymorphisms to EC risk. Odds ratios with 95% confidence intervals under five genetic models to generate the risk predicted value. The Q test and I2 statistics are used to estimate heterogeneity. Sensitivity analysis, Egger test, and Begg's funnel plot were employed to assess the results. In-silico analysis was performed to study the association between the polymorphism and mRNA expression.METHODSUp to March 2020, we searched several databases to find case-control cohorts concerned about the risk of MMPs polymorphisms to EC risk. Odds ratios with 95% confidence intervals under five genetic models to generate the risk predicted value. The Q test and I2 statistics are used to estimate heterogeneity. Sensitivity analysis, Egger test, and Begg's funnel plot were employed to assess the results. In-silico analysis was performed to study the association between the polymorphism and mRNA expression.19 case-control studies were enrolled, including 8371 EC patients and 12041 health controls. We observed the increased risk in BA vs. AA and BB + BA vs. AA models of MMP1-rs1799750 polymorphism. The protective effectiveness of EC was found in the MMP2 rs243865 polymorphism in B vs. A, BA vs. AA, and BB + BA vs. AA models. Meanwhile, the risk effect was also observed in the MMP7 rs11568818 polymorphism in most genetic models. In the furthermore bioinformatics analysis, we found that MMP1, MMP3, MMP7, MMP9, MMP12, MMP13 all increased in the tumor tissues, and the genetic alteration in the polymorphisms could impact the mRNA expression of the above MMPs.RESULTS19 case-control studies were enrolled, including 8371 EC patients and 12041 health controls. We observed the increased risk in BA vs. AA and BB + BA vs. AA models of MMP1-rs1799750 polymorphism. The protective effectiveness of EC was found in the MMP2 rs243865 polymorphism in B vs. A, BA vs. AA, and BB + BA vs. AA models. Meanwhile, the risk effect was also observed in the MMP7 rs11568818 polymorphism in most genetic models. In the furthermore bioinformatics analysis, we found that MMP1, MMP3, MMP7, MMP9, MMP12, MMP13 all increased in the tumor tissues, and the genetic alteration in the polymorphisms could impact the mRNA expression of the above MMPs.MMP1 rs1799705 and MMP7 rs1156818 polymorphisms will take part in the tumorigenesis of EC, while MMP2 rs243865 acts as a protective role to decrease the risk of EC.CONCLUSIONMMP1 rs1799705 and MMP7 rs1156818 polymorphisms will take part in the tumorigenesis of EC, while MMP2 rs243865 acts as a protective role to decrease the risk of EC.